A avaliação da aprendizagem no processo de escolarização de alunos com déficit intelectual nos anos finais do ensino fundamental e do ensino médio - Azevedo, Tânia Maria Paula de (2010)
This work is inserted into the research Field of Special Education in the Pos-Graduation Program at Federal University of Santa Maria. The central issue was the assessment of the learning of students with intellectual deficit in a school which advocate the inclusion of students with special education needs in the scholar process. When evaluating the problem, the focus was the identification of how it is processed the learning evaluation of students with intellectual deficit included in classes of final years of Fundamental and Medium School in a public School at Santa Maria/RS by professors at different areas and also, the focus was to know the results of evaluation of students in the investigated context. The study is characterized by a descriptive and exploratory approach by using the principles and procedures prescribed at Case Study, as research methodology. Data were collected from interviews, scholar documents and records of pedagogic practices, converging in the analysis of the assessment of the learning practice in the inclusion context. Countersigned the study, the inherent aspects to the assessment of the learning and the process of organization of Special Education, regarded in the scholar documents. The evaluation practices unchained by professors constituted units of analysis, at classes where there was students with intellectual deficit, one of them at Fundamental School and the other one at Medium School. The Good Practices in Special Education conducted the study, making a criteria for analysis and data interpretation, which result in the verifications that: the assessment of the learning for students with intellectual deficit is realized through differentiated strategies of evaluation level, of objectives and of the teaching; the student with intellectual deficit needs the teacher's mediation to accomplish the activities that demand the abstraction competence; the collaboration among the teachers of class and of the Special Education is facilitative of the learning and is fundamental in the articulation of the Inclusive Education.